Somatotropina bovina recombinante no desenvolvimento ponderal e sexual em bubalinos machos no período peripuberal - COELHO, Ariel de Almeida (2014)
This study aimed to verify the effect of bovine somatotrophin (bST) on sexual development, semen and endocrine traits in peripubertal buffalo. A total of 20 male Murrah buffaloes (Bubalus bubalis) (14 months of age) were randomly distributed into two treatments (bST vs control). The body weight, body condition score, testicular measurements, semen traits and IGF-I levels were evaluated once a month for a year. The ejaculate was collected by electroejaculation and physical and morphological analyzes were proceeded. Data analysis was performed using the Statistical Analysis System for Windows, SAS®. There was no difference (P>0.05) between bST and Control treatments on body weight or body condition score. Testicular measurements also showed no differences (P>0.05) between treatments, but increases significantly in a similar trend. There was no positive effect of bST treatment on age at first appearance of spermatozoa in the ejaculate (P> 0.05), but the bST group showed a significant tendency to increase the number of animals exhibiting puberty at each breeding soundness evaluation (P = 0.054). Sperm motility, vigor and percentage of abnormalities showed no difference (P>0.05). There was no difference (P>0.05) between bST and Control treatments on IGF-I serum concentrations. In conclusion, the use of bST did not result in positive effects on sexual development, semen traits and endocrine profile of male buffaloes in peripubertal period.